New insights into the reactivity of 2-halo-glycals: Synthesis of novel iodinated O- and S-glycosides. (9th November 2021) - Rojas, Agustín H.; Lafuente, Leticia; Vetere, Virginia; Ponzinibbio, Agustín
Graphical abstract: Abstract: We present the selective synthesis of new 2-iodo-2, 3-unsaturated O- and S-glycosides. This is the first report on the Ferrier rearrangement of 2-halo-glycals with S-nucleophiles. We obtained α-glycosides in good yields and with high anomeric selectivity. We also describe the particular behavior of heteroaromatic thio sugar derivatives, where the C3 addition was performed in an alternative mechanism. We present a complete structure and conformation analysis by NMR.